Bis-pyrene-modified unlocked nucleic acids: synthesis, hybridization studies, and fluorescent properties - Perlíková, Pavla; Ejlersen, Maria; Langkjaer, Niels; Wengel, Jesper (ChemMedChem, 2014)
Efficient synthesis of a building block for the incorporation of a bis-pyrene-modified unlocked nucleic acid (UNA) into oligonucleotides (DNA*) was developed. The presence of bis-pyrene-modified UNA within a duplex leads to duplex destabilization that is more profound in DNA*/RNA and less distinct in DNA*/DNA duplexes. Nevertheless, the destabilization effect of bis-pyrene-modified UNA is weaker than that of unmodified UNA. Some oligonucleotides with bis-pyrene-modified UNA incorporations displayed superior mismatch discrimination capabilities. UV/Vis absorption and molecular modeling studies indicate that the pyrene groups of bis-pyrene-modified UNA are located in the major groove of a duplex. Oligonucleotides containing two bis-pyrene-modified UNA monomers showed low pyrene monomer emission in bulge-containing duplexes, high pyrene monomer emission in fully matched duplexes, and 5-(pyrenyl)uracil:pyrene exciplex emission in the single-stranded form. Such fluorescent properties enable the application of bis-pyrene-modified UNA in the development of fluorescence probes for DNA/RNA detection and for detection of deletions at specific positions.
Keywords: fluorescence; Nucleic Acids; Models, Molecular; Fluorescence; Base Pair Mismatch; denaturace nukleových kyselin; Oligonucleotides; Pyrenes; molekulární modely; Nucleic Acid Denaturation; nukleové kyseliny; oligonukleotidy; pyreny; Spectrometry, Fluorescence; chybné párování bází; fluorescenční spektrometrie